Tunisia Poverty Assessment 2015 - World Bank (World Bank, Washington, DC, 2016)
Tunisia emerges today the only success story of the Arab Spring revolution that swept the Arab world five years ago. This poverty assessment seeks to learn from the pre and post revolution periods with a view of avoiding the repetition of past mistakes in the future. Specifically, it will provide Tunisians with a more detailed and updated diagnostics of poverty, regional disparities, trends over time and the strong links between poverty, inequality, opportunities, and vulnerability. Beyond statistics, this report will also provide a somber but more balanced alternative explanation of socioeconomic development in the country, which will hopefully complement the efforts of the Government of Tunisia to develop and implement its strategic development plan. This poverty assessment questions the extent to which growth was truly pro-poor in Tunisia and, more importantly, capable of reducing inequalities and increasing inclusion in society. This questioning sheds light on Tunisia’s prospects for a more prosperous society if substantive changes in the socioeconomic model are not introduced. The poverty assessment analysis goes into a post-2010 analysis; expanding as well the analysis of monetary poverty to broader concepts of vulnerability and equal opportunities; and by enriching traditional instruments with more sophisticated tools to measure poverty, analyze poverty dynamics, and simulate the effects of certain policy reforms for the first time in Tunisia.